Preparation method and application of conductive organic sulfur polymer micron cage
Through the preparation method of conductive organic sulfur polymer microcage, the hollow structure and short-chain sulfur components are formed by using yeast and hydrothermal reaction, which solves the low conductivity of sulfur positive electrodes and reaction kinetics in lithium-ion batteries and alkali metal-sulfur batteries. The problem of poor results enables high conductivity and excellent electrochemical performance.
Patent Information
- Application Number
- CN202411625736.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-11-14
AI Technical Summary
The capacity of the intercalated oxide cathode of lithium-ion batteries is limited and depends on rare resources. The sulfur cathode of alkali metal-sulfur batteries has problems of poor electrochemical stability and reaction kinetics.
Using the preparation method of conductive organic sulfur polymer microcage, yeast as a precursor, hollow structures and short-chain sulfur components are formed during hydrothermal reaction and heat treatment, combined with carbon-sulfur covalent structure, to enhance conductivity and electrochemistry performance.
It achieves high conductivity, excellent rate performance and high electrochemical stability. It is suitable for lithium sulfur, sodium sulfur and potassium sulfur batteries, and overcomes the problems of low conductivity and serious volume deformation of traditional sulfur positive electrodes.
Smart Images

Figure CN119490656A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic micron material synthesis, and in particular relates to a preparation method of a conductive organic sulfur polymer micron cage and application thereof. Background Art
[0002] Lithium-ion batteries are the main energy storage devices widely used today, but the intercalation oxide cathode capacity of lithium-ion batteries is usually very limited and relies on rare and expensive resources such as cobalt and nickel, leading to concerns about battery energy density and resource sustainability. Room temperature alkali metal sulfur batteries, including lithium sulfur, sodium sulfur, and potassium sulfur batteries, are based on resource-rich sulfur cathodes that, when coupled with corresponding alkali metal anodes, have ultra-high theoretical capacities (1675 mAh g -1 ). Especially for sodium-sulfur and potassium-sulfur batteries, not only are the sulfur resources of the positive electrode abundant, but the sodium and potassium resources of the negative electrode are also extremely abundant, so the advantages of cost and resource sustainability are more obvious.
[0003] Although sulfur cathodes have the advantages of high capacity and abundant resources, they face many challenges such as poor electrochemical stability and reaction kinetics. For example, cyclic S8 has long been widely studied for use in alkali metal-sulfur battery cathodes, including potassium-sulfur, sodium-sulfur, and lithium-sulfur batteries, but due to unfavorable factors such as the shuttling of long-chain soluble polysulfides, low sulfur conductivity, poor reaction kinetics, and severe electrode volume deformation, the battery cycle performance is poor and the utilization rate of sulfur is low, which hinders the practical application of alkali metal-sulfur batteries. It is worth noting that due to the large size of sodium and potassium ions, the problems of poor reaction kinetics and large volume deformation in sodium-sulfur and potassium-sulfur batteries are more serious. For example, in terms of the reactions occurring at the cathode of potassium-sulfur batteries, it is very difficult to reduce K2S3 to K2S, resulting in limited reversible capacity. At the same time, due to the formation of K2S, the theoretical volume change of the sulfur electrode is as high as 296%, which is much more serious than the value of 80% of Li2S, making it more difficult for potassium-sulfur batteries to achieve high-capacity and stable sulfur cathodes.
[0004] Converting cyclic S8 into smaller sulfur molecules (S 2-4 ) or covalent short-chain sulfur (-S x -,x≤4) strategy has achieved many successes in accelerating the reaction kinetics of sulfur cathodes and effectively improved the cycle performance of batteries. For example, Guo Yuguo's research group reported that the smaller sulfur molecules (S 2-4) confined in suitable nanopores can avoid the formation of high-order polysulfide intermediates, thereby showing better cycling performance than the cyclic S8 cathode (reference: Adv. Energy Mater. 2018, 8, 1800855). However, from the perspective of electrode material production, confining smaller sulfur molecules in porous materials usually requires strict control of the pore size, which makes the preparation process complicated and unstable. In addition, previously reported sulfur cathodes are generally only applicable to a certain type of alkali metal-sulfur battery, such as lithium-sulfur batteries. Directly transferring the high-performance sulfur cathode in lithium-sulfur batteries to another metal-sulfur battery (such as sodium-sulfur batteries or potassium-sulfur batteries) usually fails. In particular, for potassium-sulfur systems, the cycling performance of sulfur cathodes is always poor, whether they are confined in nanopores as small molecules or covalently bonded to the main chain of the host as short-chain sulfur. Therefore, it is very necessary to develop new sulfur cathodes that are suitable for various room-temperature alkali metal-sulfur batteries including lithium-sulfur, sodium-sulfur and potassium-sulfur batteries, and have excellent capacity, cycling performance and rate performance. Summary of the invention
[0005] In order to solve the above technical problems, the present invention proposes a method for preparing a conductive organic sulfur polymer microcage and its application. The method of the present invention has simple process, high production efficiency, low cost, and environmental friendliness, and overcomes the problems of low sulfur conductivity, severe volume expansion, shuttle effect, and slow kinetics existing in alkali metal-sulfur batteries. The conductive organic sulfur polymer microcage prepared by the present invention can be widely used in room temperature lithium sulfur, sodium sulfur, and potassium sulfur batteries.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] One of the technical solutions of the present invention:
[0008] A method for preparing a conductive organic sulfur polymer microcage comprises the following steps:
[0009] Dispersing yeast in acetone, stirring thoroughly, centrifuging, discarding the supernatant, and drying the precipitate to obtain acetone-treated yeast;
[0010] The acetone-treated yeast is dissolved in water, and a sodium chloride solution and a glutaraldehyde solution are added to perform a hydrothermal reaction. After the hydrothermal reaction is completed, the product is centrifuged, filtered and washed to obtain a hollow yeast-based microcage;
[0011] The hollow yeast-based microcage and sulfur powder are uniformly mixed and heat-treated under an inert atmosphere to obtain the conductive organic sulfur polymer microcage.
[0012] The present invention uses acetone to pre-wash the yeast, which can effectively destroy the cell membrane and release the substances in the cell, and then carry out the subsequent steps; the sodium chloride solution can adjust the osmotic pressure of the yeast, which is conducive to the release of the substances in the cell, and the glutaraldehyde solution plays a fixing role, and a hollow yeast-based microcage is formed after the hydrothermal reaction.
[0013] Preferably, the mass ratio of the hollow yeast-based microcage to sulfur powder is 1:(0.5-4), more preferably 1:4.
[0014] Preferably, the sulfur powder is commercial sublimated sulfur powder.
[0015] Preferably, the usage ratio of the yeast to acetone is 1 g:10 mL.
[0016] Preferably, the volume ratio of the sodium chloride solution to the glutaraldehyde solution is 25:1, the concentration of the sodium chloride solution is 100 mg / mL, and the concentration of the glutaraldehyde solution is 25 wt %.
[0017] Preferably, the temperature of the hydrothermal reaction is 190° C. and the time is 8 hours.
[0018] Preferably, the heat treatment temperature is 250-550° C., the heating rate is 1-20° C. / min, and the holding time is 1-10 h.
[0019] More preferably, the heat treatment temperature is 350°C, the heating rate is 5°C / min, and the holding time is 5h.
[0020] Preferably, the inert gas is argon, nitrogen or helium, more preferably an argon atmosphere.
[0021] The present invention mixes hollow yeast-based microcages and sulfur powder evenly, and then performs heat treatment at low temperature (250-550°C) to obtain a conductive organic sulfur polymer microcage. The microcage is not a common porous carbon material structure. The conductive organic sulfur polymer microcage of the present invention has openings on the surface and cavities inside, but has high conductivity, which can reach 7.4×10 -7 S cm -1 The sulfur component exists in the form of short-chain sulfur (S x ,x≤4), is covalently bonded to the polymer matrix by carbon and sulfur, and has abundant delocalized C=C and C=S groups, which can promote charge delocalization and improve conductivity. The sulfur content in the conductive organic sulfur polymer microcage can be as high as 46.3wt%.
[0022] The present invention proposes for the first time a method of using microbial yeast as a precursor and obtaining conductive organic sulfur polymer microcages by pyrolysis under an inert atmosphere. In view of the unique hollow structure, abundant delocalized groups and short-chain covalent sulfur of conductive organic sulfur polymers, it can not only promote the transfer of electrons, improve the conductivity of the material, and obtain high rate performance; it can also avoid the formation of soluble polysulfides, thereby avoiding the shuttle effect, achieving high storage specific capacity and high electrochemical stability. The method of the present invention has a simple and mild preparation process and high efficiency, and overcomes the problems of low conductivity of the sulfur positive electrode, severe volume deformation, shuttle effect and poor reaction kinetics in room temperature alkali metal-sulfur batteries.
[0023] The second technical solution of the present invention:
[0024] The present invention also provides a conductive organic sulfur polymer microcage prepared according to the above preparation method. The sulfur element of the conductive organic sulfur polymer microcage is covalently bonded to the carbon skeleton through CS in the form of a sulfur chain, and the particle size of the conductive organic sulfur polymer microcage is 2 to 3 μm; through elemental analyzer testing and analysis, it can be obtained that the S element content in the conductive organic sulfur polymer microcage of the present invention is 46.3wt%.
[0025] The third technical solution of the present invention:
[0026] The present invention also provides a room temperature alkali metal sulfur battery positive electrode material, comprising a conductive agent, a binder and the conductive organic sulfur polymer microcage.
[0027] Preferably, the conductive agent includes conductive carbon black (Super P), acetylene black (Acetylene Black) or carbon nanotubes (CNT), more preferably Super P.
[0028] Preferably, the binder comprises: sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) mixed in equal weight ratio, or polyacrylic acid (PAA), or polyvinylidene fluoride (PVDF), more preferably CMC and SBR mixed in equal weight ratio.
[0029] Preferably, the mass ratio of the conductive organic sulfur polymer microcage, the conductive agent and the binder is (80-60): (3-30): (5-20), more preferably (60-80): (10-25): (8-20), such as 70:20:10, or 75:15:10.
[0030] The fourth technical solution of the present invention:
[0031] The present invention also provides the use of the conductive organic sulfur polymer microcage in preparing positive electrode materials for room temperature alkali metal sulfur batteries.
[0032] The fifth technical solution of the present invention:
[0033] The present invention also provides the use of the conductive organic sulfur polymer microcage in the preparation of potassium sulfur batteries, sodium sulfur batteries or lithium sulfur batteries.
[0034] Preferably, the potassium-sulfur battery comprises a negative electrode, an electrolyte and the room temperature alkali metal sulfur battery positive electrode material.
[0035] Preferably, the sodium-sulfur battery comprises a negative electrode, an electrolyte and the room temperature alkali metal sulfur battery positive electrode material.
[0036] Preferably, the lithium-sulfur battery comprises a negative electrode, an electrolyte and the room temperature alkali metal sulfur battery positive electrode material.
[0037] Compared with the prior art, the present invention has the following advantages and technical effects:
[0038] (1) The conductive organic sulfur polymer microcage positive electrode prepared by the present invention can show excellent electrochemical performance in potassium-sulfur batteries. -1 The first cycle potassium storage capacity of the organic sulfur polymer cathode is as high as 1206.5 mAh g -1 ; at 1.8A·g -1 The potassium storage capacity at the current density is 371 mAh g -1 , has excellent rate performance; at 0.9A·g -1 The capacity retention rate is as high as 99% after 1100 cycles at the current density, which has excellent cycle performance.
[0039] (2) The conductive organic sulfur polymer microcage positive electrode prepared by the present invention can also exhibit excellent electrochemical performance in sodium-sulfur batteries. -1 The first cycle sodium storage reversible capacity of the organic sulfur polymer cathode is as high as 1348.3 mAh g -1 ; at 3.6A·g -1 At a current density of 1.5 %, the sodium storage capacity reaches 355.9 mAh g -1 , with excellent rate performance; at 0.9A·g -1 After cycling for more than 450 times at the current density, the capacity retention rate is 90%, which has excellent cycle performance.
[0040] (3) The conductive organic sulfur polymer microcage positive electrode prepared by the present invention can also exhibit excellent electrochemical performance in lithium-sulfur batteries. -1 The first cycle lithium storage reversible capacity of the organic sulfur polymer cathode is as high as 1153.4 mAh g -1 ; at 3.6A·g -1At a current density of 1.34 W, the lithium storage capacity reaches 447.1 mAh g -1 , with excellent rate performance; at 0.6A·g -1 The capacity retention rate was 91% after more than 350 cycles at the current density. The prepared conductive organic sulfur polymer microcage also has excellent cycle performance as the positive electrode of lithium-sulfur battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] The accompanying drawings constituting a part of this application are used to provide a further understanding of this application. The illustrative embodiments and descriptions of this application are used to explain this application and do not constitute an improper limitation on this application. The capacity marked in the following drawings refers to the reversible specific capacity, and the marked efficiency refers to the coulombic efficiency. In the accompanying drawings:
[0042] Figure 1 The flowchart of the preparation of the conductive organic sulfur polymer microcage of the present invention is as follows;
[0043] Figure 2 is a transmission electron microscopy image of the conductive organosulfur polymer microcage prepared in Example 1;
[0044] Figure 3 Element distribution diagram of the conductive organic sulfur polymer microcage prepared in Example 1;
[0045] Figure 4 is a Raman spectrum of the conductive organic sulfur polymer microcage prepared in Example 1;
[0046] Figure 5 The potassium-sulfur battery prepared in Example 5 is 0.03A·g -1 The first cycle charge and discharge curve at the current density of;
[0047] Figure 6 The potassium-sulfur battery prepared in Example 5 is 0.15A·g -1 Schematic diagram of the cycling performance after 50 cycles at a current density of;
[0048] Figure 7 The potassium-sulfur battery prepared in Example 5 is 0.9A·g -1 Schematic diagram of the cycle performance after 1100 cycles at a current density of ;
[0049] Figure 8 This is a rate performance diagram of the potassium-sulfur battery prepared in Example 5 under different current density conditions;
[0050] Fig. 9 The sodium-sulfur battery prepared in Example 6 is 0.03A·g -1 The first cycle charge and discharge curve at the current density of;
[0051] Fig.10 This is a rate performance diagram of the sodium-sulfur battery prepared in Example 6 under different current density conditions;
[0052] Fig.11 The sodium-sulfur battery prepared in Example 6 is 0.06A·g -1 Schematic diagram of the cycling performance after 120 cycles at a current density of ;
[0053] Fig.12 The sodium-sulfur battery prepared in Example 6 is 0.9A·g -1 Schematic diagram of the cycling performance of more than 450 cycles at a current density of ;
[0054] Fig.13 The lithium-sulfur battery prepared in Example 7 is 0.03A·g -1 The first cycle charge and discharge curve at the current density of;
[0055] Fig.14 The lithium-sulfur battery prepared in Example 7 is -1 Schematic diagram of the cycling performance after more than 350 cycles at a current density of ;
[0056] Fig.15 This is a rate performance diagram of the lithium-sulfur battery prepared in Example 7 under different current density conditions;
[0057] Fig.16 This is a scanning electron microscope image of the amorphous carbon material prepared in Comparative Example 1, a is 2 μm, b is 1 μm;
[0058] Fig.17 is a Raman spectrum of the amorphous carbon material prepared in Comparative Example 1;
[0059] Fig.18 is a Raman spectrum of the conductive organic sulfur polymer prepared in Comparative Example 2;
[0060] Fig.19 Schematic diagram of preparing conductive organic sulfur polymer microcages in Example 1 and preparing carbon microcage / S8 composites in Comparative Example 3;
[0061] Fig. 20 The XRD pattern of the conductive organosulfur polymer microcage prepared in Example 1;
[0062] Fig.21 The electrochemical behavior diagram of the conductive organic sulfur polymer microcage prepared in Example 1 as the positive electrode material of the lithium-sulfur battery in Example 8, wherein a is the conductive organic sulfur polymer microcage at 0.03Ag -1 The first and third charge-discharge curves under the conditions of (a) and (b) are the charge-discharge curves of the conductive organic sulfur polymer microcage under the conditions of a scan rate of 0.1 mV s -1Cyclic voltammetry (CV) curves. DETAILED DESCRIPTION
[0063] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0064] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0065] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0066] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0067] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0068] Unless otherwise specified, the room temperature in the present invention is 25±2°C.
[0069] Unless otherwise specified, the experimental materials, reagents, instruments, etc. used in the embodiments of the present invention are all commercially available; unless otherwise specified, all technical means in the embodiments of the present invention are conventional means well known to those skilled in the art.
[0070] The core of the present invention is to provide a method for obtaining conductive organic sulfur polymer microcages by using hollow yeast-based microspheres of a single component which are directly synthesized without any post-modification as a precursor, mixing them evenly with sulfur powder, and then pyrolyzing them in an inert atmosphere in one step.
[0071] The present application provides a method for preparing a conductive organic sulfur polymer microcage, and the preparation flow chart thereof is as follows: Figure 1 As shown, the specific steps include:
[0072] S01: Disperse the yeast in acetone, stir thoroughly, centrifuge and discard the supernatant, transfer the precipitate to an oven and dry it to obtain acetone pre-washed yeast;
[0073] S02: dissolving the yeast pre-washed with acetone in water, adding sodium chloride solution and glutaraldehyde solution, stirring evenly and transferring to a reactor, placing the reactor in an oven at 190°C for hydrothermal reaction for 8 hours, repeating centrifugation, filtering and washing three times after the reaction to obtain a brown solid product (hollow yeast-based microcage);
[0074] S03: The obtained brown solid product and commercial sublimated sulfur powder are ground and mixed evenly, and heat-treated under inert atmosphere to obtain conductive organic sulfur polymer microcages.
[0075] The hollow yeast-based microcages and commercial sublimated sulfur powder are heat-treated at a temperature of 250-550° C., preferably 350° C., under inert atmosphere conditions, and the heating rate during the heat treatment is 0.5° C. / min-20° C. / min, preferably 5° C. / min. The inert gas is argon, nitrogen or helium.
[0076] The technical solution of the present invention is further illustrated by the following embodiments.
[0077] Example 1
[0078] This embodiment provides a method for preparing a conductive organic sulfur polymer microcage:
[0079] S01: Disperse 1.0 g of yeast in 10 mL of acetone, stir for 30 min, centrifuge and discard the supernatant, place the precipitate in an oven and dry at 50 °C to obtain acetone pre-washed yeast;
[0080] S02: The yeast pre-washed with acetone was dissolved in 30 mL of water, 5 mL of sodium chloride solution (100 mg / mL) and 200 μL of glutaraldehyde solution (concentration of 25 wt%) were added, and the mixture was transferred to a 50 mL reactor after stirring evenly. The reactor was placed in an oven for hydrothermal reaction at 190°C for 8 hours. After the reaction was completed, centrifugation, filtration and washing were repeated three times to obtain hollow yeast-based microspheres;
[0081] S03: The obtained hollow yeast-based microspheres and commercial sublimated sulfur powder were uniformly mixed in a mass ratio of 1:4, and heat-treated at 350°C for 5 h in an argon atmosphere at a heating rate of 5°C / min to obtain conductive organic sulfur polymer microcages.
[0082] The transmission electron microscopy image of the conductive organic sulfur polymer microcage prepared in this example is shown in Figure 2 , element distribution diagram see Figure 3 , Raman spectrum is shown in Figure 4 It can be seen that the sulfur element in the conductive organic sulfur polymer microcage is covalently bonded to the carbon skeleton in the form of sulfur chains through CS, and the particle size of the conductive organic sulfur polymer microcage is 2-3μm; the S element content in the conductive organic sulfur polymer microcage is 46.3wt%.
[0083] Example 2
[0084] This embodiment provides a method for preparing a conductive organic sulfur polymer microcage:
[0085] S01: Disperse 1.0 g of yeast in 10 mL of acetone, stir for 30 min, centrifuge and discard the supernatant, place the precipitate in an oven and dry at 50 °C to obtain acetone pre-washed yeast;
[0086] S02: The yeast pre-washed with acetone was dissolved in 30 mL of water, 5 mL of sodium chloride solution (100 mg / mL) and 200 μL of glutaraldehyde solution (concentration of 25 wt%) were added, and the mixture was transferred to a 50 mL reactor after stirring evenly. The reactor was placed in an oven for hydrothermal reaction at 190°C for 8 hours. After the reaction was completed, centrifugation, filtration and washing were repeated three times to obtain hollow yeast-based microspheres;
[0087] S03: The obtained hollow yeast-based microspheres and commercial sublimated sulfur powder were uniformly mixed in a mass ratio of 1:4, and heat-treated at 250°C for 10 h in a nitrogen atmosphere at a heating rate of 10°C / min to obtain conductive organic sulfur polymer microcages.
[0088] Example 3
[0089] This embodiment provides a method for preparing a conductive organic sulfur polymer microcage:
[0090] S01: Disperse 1.0 g of yeast in 10 mL of acetone, stir for 30 min, centrifuge and discard the supernatant, place the precipitate in an oven and dry at 50 °C to obtain acetone pre-washed yeast;
[0091] S02: The yeast pre-washed with acetone was dissolved in 30 mL of water, 5 mL of sodium chloride solution (100 mg / mL) and 200 μL of glutaraldehyde solution (concentration of 25 wt%) were added, and the mixture was transferred to a 50 mL reactor after stirring evenly. The reactor was placed in an oven for hydrothermal reaction at 190°C for 8 hours. After the reaction was completed, centrifugation, filtration and washing were repeated three times to obtain hollow yeast-based microspheres;
[0092] S03: The obtained hollow yeast-based microspheres and commercial sublimated sulfur powder were uniformly mixed in a mass ratio of 1:4, and heat-treated at 550°C for 1 h in a helium atmosphere at a heating rate of 20°C / min to obtain conductive organic sulfur polymer microcages.
[0093] Example 4
[0094] The same as Example 1, except that the hollow yeast-based microspheres and commercial sublimated sulfur powder in S03 are uniformly mixed in a mass ratio of 1:0.5.
[0095] Example 5
[0096] This embodiment provides a preparation process of a positive electrode sheet of a potassium-sulfur battery and a method for assembling a battery:
[0097] S01: The conductive organic sulfur polymer microcage in Example 1 is used as a positive electrode material, and is evenly mixed with a conductive agent Super P and a binder in a mass ratio of 70:20:10, and a mixture of CMC and SBR in a mass ratio of 1:1 is used as a binder. Deionized water is added in an amount of 150 μL deionized water / 100 mg active material (i.e., conductive organic sulfur polymer microcage, the same below), and a uniform slurry is formed by mechanical stirring. The slurry is coated on an aluminum foil and dried under vacuum for 6 hours to obtain a positive electrode sheet;
[0098] S02: Cut the dried positive electrode sheet into a circular electrode sheet with a diameter of 10 mm;
[0099] S03: The obtained circular electrode sheet is used as the positive electrode of the potassium-sulfur battery, the glass fiber membrane is used as the battery separator, 2.5M KFSI TEP is used as the electrolyte, and it is assembled with metallic potassium into a button battery. The specification of the button battery is CR2032.
[0100] Battery performance test:
[0101] The potassium-sulfur battery prepared in this embodiment was subjected to a constant current charge and discharge test using a battery charge and discharge tester, the test voltage range was 0.5-3V, and the temperature of the test environment was 25°C. Figure 5 The potassium-sulfur battery of this embodiment is 0.03A·g -1 The first cycle charge and discharge curve at a current density of 1.38 Å, and the reversible capacity of the first cycle is as high as 1206.5 mAh g -1 , which has a high reversible specific capacity. Figure 6 The potassium-sulfur battery in this embodiment is 0.15A·g -1 Schematic diagram of the cycling performance after 50 cycles under current density conditions. Figure 7 The potassium-sulfur battery of this embodiment is 0.9A·g -1Schematic diagram of the cycling performance after 1100 cycles at the same current density, with a capacity retention rate of 99%. Figure 8 The rate performance diagram of the potassium-sulfur battery of this embodiment under different current density conditions is shown in FIG. -1 At a current density of 1.34 W, the specific capacity reaches 371 mAh g -1 It can be seen that the conductive organic sulfur polymer microcage prepared by the present invention has excellent rate performance as the positive electrode of potassium-sulfur battery.
[0102] Example 6
[0103] This embodiment provides a preparation process of a sodium-sulfur battery positive electrode sheet and a battery assembly method:
[0104] S01: The conductive organic sulfur polymer microcage in Example 1 is used as the positive electrode material, and is evenly mixed with the conductive agent Super P and the binder at a mass ratio of 70:20:10, and a mixture of CMC and SBR at a mass ratio of 1:1 is used as the binder. Deionized water is added in an amount of 150 μL deionized water / 100 mg active material, and a uniform slurry is formed by mechanical stirring. The slurry is coated on aluminum foil and dried under vacuum for 6 hours to obtain a positive electrode sheet;
[0105] S02: Cut the dried positive electrode sheet into a circular electrode sheet with a diameter of 10 mm;
[0106] S03: The obtained circular electrode sheet is used as the positive electrode of the sodium-sulfur battery, the glass fiber membrane is used as the battery separator, 1M NaPF6 EC PC is used as the electrolyte, and it is assembled with metallic sodium into a button battery. The specification of the button battery is CR2032.
[0107] Battery Test:
[0108] A constant current charge and discharge test was performed on the sodium-sulfur battery prepared in this embodiment using a battery charge and discharge tester, the test voltage range was 0.5-2.8V, and the temperature of the test environment was 25°C. Fig. 9 The sodium-sulfur battery of this embodiment is 0.03A·g -1 The first cycle charge and discharge curve at a current density of 1.38 Å / min, and the reversible capacity of sodium storage in the first cycle is as high as 1348.3 mAh g -1 , which has a high reversible specific capacity. Fig.10 The rate performance diagram of the sodium-sulfur battery of this embodiment under different current density conditions is shown in FIG. -1 At a current density of 1.34 W, the specific capacity reaches 355.9 mAh g -1 , which has excellent rate performance. Fig.11 The sodium-sulfur battery in this embodiment is tested at a rate of 0.06A·g -1Schematic diagram of the cycling performance after 120 cycles under current density conditions. Fig.12 The sodium-sulfur battery of this embodiment is 0.9A·g -1 The schematic diagram of the cycle performance of more than 450 cycles under the current density is shown, and the capacity retention rate is 90%. It can be seen that the conductive organic sulfur polymer microcage prepared by the present invention also has excellent cycle stability as the positive electrode of the sodium-sulfur battery.
[0109] Example 7
[0110] This embodiment provides a preparation process of a positive electrode sheet of a lithium-sulfur battery and a method for assembling a battery:
[0111] S01: The conductive organic sulfur polymer microcage in Example 1 is used as the positive electrode material, and is evenly mixed with the conductive agent Super P and the binder at a mass ratio of 70:20:10, and a mixture of CMC and SBR at a mass ratio of 1:1 is used as the binder. Deionized water is added in an amount of 150 μL deionized water / 100 mg active material, and a uniform slurry is formed by mechanical stirring. The slurry is coated on aluminum foil and dried under vacuum for 6 hours to obtain a positive electrode sheet;
[0112] S02: Cut the dried positive electrode sheet into a circular electrode sheet with a diameter of 10 mm;
[0113] S03: The obtained circular electrode sheet is used as the positive electrode of the lithium-sulfur battery, the glass fiber membrane is used as the battery separator, 5M LiFSI EC EMC is used as the electrolyte, and it is assembled with metallic lithium into a button battery. The specification of the button battery is CR2032.
[0114] Battery Test:
[0115] The lithium-sulfur battery prepared in this embodiment was subjected to constant current charge and discharge test using a battery charge and discharge tester. The test voltage range was 1 to 3 V, and the temperature of the test environment was 25° C. Fig.13 The lithium-sulfur battery of this embodiment is 0.03A·g -1 The first cycle charge and discharge curve at a current density of 1.5 %. The first cycle reversible lithium storage capacity is as high as 1153.4 mAh g -1 , which has a high reversible specific capacity. Fig.14 The lithium-sulfur battery of this embodiment is 0.6A·g -1 Schematic diagram of the cycling performance after more than 350 cycles at the same current density, with a capacity retention rate of 91%. Fig.15 The rate performance diagram of the lithium-sulfur battery of this embodiment under different current density conditions is shown in FIG. -1 At a current density of 1.34 W, the specific capacity reaches 447.1 mAh g -1It can be seen that the conductive organic sulfur polymer microcage prepared by the present invention also has excellent rate performance as the positive electrode of lithium-sulfur battery.
[0116] Example 8
[0117] The same as Example 7, except that the electrolyte in this example is 1M LiTFSIDOL DME (volume ratio 1:1) electrolyte, which contains 2wt% LiNO3 as an electrolyte additive.
[0118] Comparative Example 1
[0119] S01: Disperse 1.0 g of yeast in 10 mL of acetone, stir for 30 min, centrifuge and discard the supernatant, place the precipitate in an oven and dry at 50 °C to obtain acetone pre-washed yeast;
[0120] S02: The yeast pre-washed with acetone was dissolved in 30 mL of water, 5 mL of sodium chloride solution (100 mg / mL) and 200 μL of glutaraldehyde solution (concentration of 25 wt%) were added, and the mixture was transferred to a 50 mL reactor after stirring evenly. The reactor was placed in an oven for hydrothermal reaction at 190°C for 8 hours. After the reaction was completed, centrifugation, filtration and washing were repeated three times to obtain hollow yeast-based microspheres;
[0121] S03: The obtained hollow yeast-based microspheres were heat treated at 350° C. for 5 h under an argon atmosphere with a heating rate of 5° C. / min to obtain an amorphous carbon microcage material.
[0122] The scanning electron microscope image of the amorphous carbon material prepared in this comparative example is shown in Fig.16 , Raman spectrum is shown in Fig.17 The Raman spectrum shows a D peak induced by defects and a G peak induced by graphite corresponding to the amorphous carbon material, and no peaks corresponding to CS, SS, C=S and S=S appear. The particle size of the amorphous carbon material is 2 to 3 μm. Since no sulfur powder is added during the heat treatment in this comparative example, an amorphous carbon material is obtained.
[0123] Comparative Example 2
[0124] Same as Example 1, except that the heat treatment temperature in S03 is 800°C.
[0125] The Raman spectrum of this comparative example is shown in Fig.18 From the obvious D peak and G peak, it can be seen that the conductive organic sulfur polymer is carbonized due to the excessively high heat treatment temperature of this comparative example.
[0126] Comparative Example 3
[0127] The same as comparative example 1, except that the amorphous carbon microcage material and sulfur powder obtained in comparative example 1 are mixed according to a weight ratio of 53.7:46.3, then put into a glass tube, evacuate and seal, and then heat at 155°C for 12h to finally obtain a carbon microcage / S8 composite material.
[0128] Schematic diagrams of the preparation of conductive organic sulfur polymer microcages in Example 1 and the preparation of carbon microcage / S8 composites in Comparative Example 3 are shown in Fig.19 It can be seen that the present invention (left side) uses a chemical bonding method to form a conductive organic sulfur polymer microcage, short-chain sulfur (-S 1-4 -) will bond to the formed polymer, which is different from the right side where the S8 molecules are physically confined or loaded to finally form a carbon microcage / S8 complex.
[0129] The XRD pattern of the conductive organic sulfur polymer microcage prepared in Example 1 is shown in Fig. 20 It can be seen that the conductive organic sulfur polymer microcage prepared in the present invention has no diffraction peak signal of S8, while the carbon microcage / S8 composite in Comparative Example 3 has a strong diffraction peak.
[0130] The electrochemical behavior of the conductive organic sulfur polymer microcage prepared in Example 1 as a lithium sulfur battery is shown in Example 8. Fig.21 , where (a) is a conductive organic sulfur polymer microcage at 0.03Ag -1 The first and third charge-discharge curves under the conditions of (a) and (b) are the first and third charge-discharge curves under the conditions of (b) and (c) the first and third charge-discharge curves under the conditions of (c) and (d) the first and third charge-discharge curves under the conditions of (d) and (e) the first and third charge-discharge curves under the conditions of (e) and (f) the first and third charge-discharge curves under the conditions of (f) and (g) -1 Cyclic voltammetry (CV) curve under . It is well known that long-chain sulfur (Sx, x>4) or cyclic S8 positive electrode will have a voltage platform above ~2.3V during the discharge process of lithium battery (reference: Matter 2023, 6(2), 316 and Angew.Chem.Int.Ed.2019, 58(52), 18746), indicating that the solid-liquid reaction leads to the formation of long-chain polysulfide (Li2S x , x>4). For the conductive organosulfur polymer microcages, no high-voltage (>2.2V) platform was observed during the discharge process, and there was no corresponding reduction peak in the CV curve. Instead, there were only low-voltage (<2.1V) capacity and reaction peaks related to the formation of short-chain polysulfides (Li2Sx, x≤4), indicating that the sulfur species bound in the conductive organosulfur polymer microcages were short-chain sulfur (Sx, x≤4).
[0131] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing a conductive organic sulfur polymer microcage, characterized in that: The following steps are involved: Dispersing yeast in acetone, stirring thoroughly, centrifuging, discarding the supernatant, and drying the precipitate to obtain acetone-treated yeast; The acetone-treated yeast is dissolved in water, and a sodium chloride solution and a glutaraldehyde solution are added to perform a hydrothermal reaction. After the hydrothermal reaction is completed, the product is centrifuged, filtered and washed to obtain a hollow yeast-based microcage; The hollow yeast-based microcage and sulfur powder are uniformly mixed and heat-treated under an inert atmosphere to obtain the conductive organic sulfur polymer microcage.
2. The method for preparing the conductive organic sulfur polymer microcage according to claim 1, characterized in that: The usage ratio of the yeast and acetone is 1 g:10 mL.
3. The method for preparing the conductive organic sulfur polymer microcage according to claim 1, characterized in that: The volume ratio of the sodium chloride solution to the glutaraldehyde solution is 25:
1.
4. The method for preparing the conductive organic sulfur polymer microcage according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 190° C. and the time is 8 hours.
5. The method for preparing the conductive organic sulfur polymer microcage according to claim 1, characterized in that: The heat treatment temperature is 250-550° C., the heating rate is 1-20° C. / min, and the heat preservation time is 1-10 hours.
6. The method for preparing the conductive organic sulfur polymer microcage according to claim 1, characterized in that: The mass ratio of the hollow yeast-based micro-cage to the sulfur powder is 1:(0.5-4).
7. A conductive organic sulfur polymer microcage, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 6.
8. A room temperature alkali metal sulfur battery positive electrode material, characterized in that: The method comprises a conductive agent, a binder and the conductive organic sulfur polymer microcage according to claim 7.
9. Use of the conductive organic sulfur polymer microcage according to claim 7 in preparing positive electrode materials for room temperature alkali metal sulfur batteries.
10. Use of the conductive organic sulfur polymer microcage according to claim 7 in the preparation of potassium sulfur batteries, sodium sulfur batteries or lithium sulfur batteries.
Citation Information
Patent Citations
Positive electrode material of lithium sulfur battery, preparation method of positive electrode material and lithium sulfur battery containing positive electrode material
CN106450195A
Biomass carbon microsphere, preparation method, supercapacitor and application
CN112357904A
Lithium-sulfur battery positive electrode material and preparation method thereof, lithium-sulfur battery positive electrode and lithium-sulfur battery
CN114864902A
Preparation method of sulfur-rich polymer hierarchical pore carbon nanocage composite material and application of sulfur-rich polymer hierarchical pore carbon nanocage composite material in lithium-sulfur battery
CN115566161A
Preparation method and application of monatomic sulfur-carbon compound
CN116190601A